Sebaran Pergerakan Pengguna Kendaraan Pribadi Bekasi Barat-DKI Jakarta - Herawati, Herawati; Suliyatni, Rini (Sekretariat Badan Penelitian dan Pengembangan Perhubungan, 2012)
The high traffic in OKI Jakarta is not only influenced by mavements in but also commuters from sub-urban areas like Bekasi District. For that we need to know the characteristics and distribution of the movement from North Bekasi to Jakarta. The purpose of this study was to determine the distribution of travelling from Bekasi to Jakarta. The research methods used are the establishment of Inter-Zone Travel Time Matrix, trip generation modeling (multiple regression analysis), Travel Distribution Modeling. In addition, the quantity method is used to identify travel time, total travel costs and advanced modes are used when using public transport. Based on the results obtained by the analysis of trip generation models Y = -1.44 of public transport + 2:14 of private vehicles. Trip distribution of Bekasi's population towards OKI Jakarta are Central Jakarta (261 trips/day), East Jakarta (180 trips/ day), South Jakarta (125 trip/day), West Jakarta (74 trips/day), and East Jakarta (87 trips/day). The different of travel time between private vehicles and public transport is average 30 minutes. Private vehicle users must expend more vehicle surcharge of Rp. 11 553 which compared with public transport.